ANALISIS EFISIENSI TATANIAGA BAHAN OLAH KARET (BOKAR) DI DESA SUMBU SARI KECAMATAN MESUJI RAYA KABUPATEN OGAN KOMERING ILIR PROPINSI SUMATERA SELATAN - Lestari lestari (Program Studi Agribisnis Faperta Universitas Muhammadiyah Bengkulu, 2020)
Efficiency Analysis of Rubber Sports Materials (Bokar) in Sumbu Sari Village, Mesuji Raya District, Ogan Komering Ilir Regency.Â This study aims to find out how the channels of community rubber trading in Sumbu Sari Village, Mesuji Raya District, Ogan Komering Ilir Regency, and calculating how much the level of trading efficiency of rubber processing materials (bokar) in Sumbu Sari Village is seen from the trading margin, the trading advantages and the share received by the farmers. This research was carried out in August 2018.The sampling method in this study is the sampling method used is simple random (Random sampling). Sampling was carried out on rubber farmers whose rubber plants were around 10 to 15 years old with an average land area of 2 ha and a population of 100 heads of rubber farmers in Sumbu Sari Village. While the sample was taken 20 percent, the number of farmers sampled was 20 rubber farmers as respondents.The results of this study indicate that there is a trading channel that involves two intermediary institutions, namely wholesalers and factories / exporters (PT. Hevea MK II) as the final consumers in the Rubber Material Material Trading Channel (BOKAR) in Sumbu Sari Village, Mesuji Raya District, Ogan Regency. Komering Ilir and the level of efficiency of the trading system for Rubber Sports Materials (BOKAR) which is 33.28% (efficient) with the farmer's share of the trade of 57.14% and the total trading margin of Rp. 6,000 contained in the trading channel in Sumbu Sari Village, Mesuji Raya District, Ogan Komering Ilir Regency. This shows that short trading channels are more efficient than long trading channels.Â Key words : efficiency, Bokar, rubber